RNA Viral Vectors for Accelerating Plant Synthetic Biology - Khakhar, Arjun; Voytas, Daniel F. (Frontiers in Plant Science, 2021)
The tools of synthetic biology have enormous potential to help us uncover the fundamental mechanisms controlling development and metabolism in plants. However, their effective utilization typically requires transgenesis, which is plagued by long timescales and high costs. In this review, we explore how transgenesis can be minimized by delivering foreign genetic material to plants with systemically mobile and persistent vectors based on RNA viruses. We examine the progress that has been made thus far and highlight the hurdles that need to be overcome and some potential strategies to do so. We conclude with a discussion of biocontainment mechanisms to ensure these vectors can be used safely as well as how these vectors might expand the accessibility of plant synthetic biology techniques. RNA vectors stand poised to revolutionize plant synthetic biology by making genetic manipulation of plants cheaper and easier to deploy, as well as by accelerating experimental timescales from years to weeks.